Effect of Steroids on the Progression of Alzheimer's Dementia: A Retrospective Chart Review - Julijana Zoran Conic; Alexandra Chetty; Lily Chen; Audrey Marsh; Sean Barry; Rodney Pattabhi; Thomas Reske; Erwin Aguilar; Lobna Ali (Aging Medicine)
ABSTRACT Objectives Alzheimer's disease (AD) is a prevalent age‐related neurodegenerative disease that affects millions of individuals in the United States. Neuroinflammation is a driver of the neurodegenerative changes that characterize AD, prompting interest in how inflammation can be modulated for treatment and prevention. Methods ICD‐10 codes were quarried from electronic medical records to identify patients diagnosed with AD from 2012 to 2020. The patients were then divided into those who used systemic steroids and those who did not before the progression of their disease. Data on medication prescribed was used to measure the disease's progression. Clinical findings and laboratory results were collected to build a propensity score. Patients were followed until disease progression, death, or the last available visit. Kaplan–Meier curves and hazard ratios adjusted for the propensity score were used to compare the two groups. Results Of the 459 patients identified, 77 were included in the study, and 13 used steroids. Of the 77 patients included in the study, 59 had progression of their disease, and of those, five used steroids. The median time to progression was 408.00 (191.00, 979.00) days for the overall sample. The hazard ratio (HR) comparing the group using steroids to those not using steroids was 0.26 with a 95% CI of (0.1013, 0.673) and a p value of 0.00064. Conclusions In our study, steroid use delayed the progression of dementia. Further study is needed to outline how steroids and anti‐inflammatory medications can be used in the treatment and prevention of AD.